PELATIHAN KARTU ANGKA BERGAMBAR DALAM MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK USIA PRA SEKOLAH - Dwi Indarti; Komsiyah Komsiyah; Mustika Marahayu; Nurisda Eva Irmawati; Zuniati Zuniati; Marwiati Marwiati (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2022)
Inappropriate learning methods can cause a decrease in children's learning motivation, the lack of understanding of teachers and parents in improving cognitive development in children can result in poor child development. To overcome this problem, appropriate intervention is needed. As the practice of the Tridarma of higher education, a lecturer must do community service. One of the services that has been carried out is a community service activity with the title